2022
DOI: 10.12669/pjms.39.1.5485
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition among patients with Type-2 Diabetes Mellitus

Abstract: Objectives: The present study aims to evaluate the nutritional status of diabetic patients using Subjective Global Assessment (SGA) tool. Methods: A prospective cross-sectional study was conducted at Endocrine and Medicine Department of Lady Reading Hospital from September 2019 to March 2020. A total of 359 patients diagnosed with Type-2 Diabetes Mellitus (T2DM) were included in the study. The malnutrition status was assessed using SGA, and clinical parameters including albumin and total leukocyte count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Thought, the T2DM patients suffered from the weight loss. the BMI was still high and also were assessed as malnourished, which better agree with the conclusions that the incidence of malnutrition in obese patients is much lower than that in underweight patients 9 . The education level of University and above (OR = 0.53, 95% CI = 0.286 -0.981) is an independent protective factor against malnutrition in patients with T2DM.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thought, the T2DM patients suffered from the weight loss. the BMI was still high and also were assessed as malnourished, which better agree with the conclusions that the incidence of malnutrition in obese patients is much lower than that in underweight patients 9 . The education level of University and above (OR = 0.53, 95% CI = 0.286 -0.981) is an independent protective factor against malnutrition in patients with T2DM.…”
Section: Discussionsupporting
confidence: 87%
“…Ahmed et al 9 pointed out that the malnutrition risk does not differ by gender. Another systematic comments showed that females have 45% greater OR of being malnourished compared to males 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se identificó a la mayoría de los pacientes evaluados con neuropatía diabética en riesgo de desnutrición, lo cual guarda correlación con investigaciones nacionales e internacionales. 11,18,19 Asimismo, hasta donde es de nuestro conocimiento, se encuentra poca información acerca del estado nutricional en pacientes con neuropatía diabética, por lo que este estudio puede ser de utilidad para entender aún más estos procesos.…”
Section: Discussionunclassified
“…According to the KDIGO clinical practice guidelines, CKD was diagnosed that glomerular filtration rate (GFR) below 60 mL/min/1.73 m 2 for 3 months or more 15 . (4) Missing BUN or serum albumin values; (5) Less than 48 h in ICU; (6) Missing data for more than 5% of patients. Finally, a total of 1920 patients were included in this study (Fig.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%